2018
DOI: 10.48550/arxiv.1812.00703
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast Nonlinear Fourier Transform Algorithms Using Higher Order Exponential Integrators

Shrinivas Chimmalgi,
Peter J. Prins,
Sander Wahls

Abstract: The nonlinear Fourier transform (NFT) has recently gained significant attention in fiber optic communications and other engineering fields. Although several numerical algorithms for computing the NFT have been published, the design of highly accurate low-complexity algorithms remains a challenge. In this paper, we present new fast forward NFT algorithms that achieve accuracies that are orders of magnitudes better than current methods, at comparable run times and even for moderate sampling intervals. The new al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…The accuracy-complexity trade-off, however, is similar for the two methods. Finally, we also present a fast variant of the CF method of order four (formally) by employing the fourth order splitting on the lines of [6], [10]. Despite the well-known limitation imposed on the order and stability of such techniques as demonstrated by Sheng [11], we do not find any reduction of order within the double precision arithmetic.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The accuracy-complexity trade-off, however, is similar for the two methods. Finally, we also present a fast variant of the CF method of order four (formally) by employing the fourth order splitting on the lines of [6], [10]. Despite the well-known limitation imposed on the order and stability of such techniques as demonstrated by Sheng [11], we do not find any reduction of order within the double precision arithmetic.…”
Section: Introductionmentioning
confidence: 91%
“…Despite the well-known limitation imposed on the order and stability of such techniques as demonstrated by Sheng [11], we do not find any reduction of order within the double precision arithmetic. It is noteworthy that the authors in [6] found the aforementioned splitting worsen in accuracy after a certain step-size. It is also not clear from their analysis if this scheme is convergent in their setting.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this Letter, we will focus on building the method of the fourth order of accuracy on a uniform grid. For a non-uniform grid, a fourth order scheme [10] was applied in [11]. In perspective, the exponential approximation can be applied to our scheme so that we can use the fast algorithm.…”
mentioning
confidence: 99%
“…However there are indications that the burst length cannot be increased indefinitely without degradation in performance [10]. At the same time, the development of fast and accurate algorithms for the forward nonlinear Fourier transform continues [11]- [13].…”
mentioning
confidence: 99%